DNA methylation and mRNA expression of IGF‐1 and MMP‐2 after form‐deprivation myopia in guinea pigs. (3rd June 2020) - Ding, Xuan; Fu, Dan; Ge, Shichao; Guan, Qinghua; Chen, Minjie; Yu, Zhiqiang
Abstract: Purpose: The molecular mechanism of form‐deprivation myopia is unclear. This study was aimed to investigate the roles of scleral DNA methylation and mRNA expression of IGF‐1 and MMP‐2 in a guinea pig model of form‐deprivation myopia. Methods: Seventy 2‐week‐old male guinea pigs were assigned to three groups: (1) zero week group that was used to collect baseline data; (2) monocular deprivation treatment (MDT) group, in which a thin slice of opaque latex glove was placed over the right eyes of the animals for four weeks, and the left eyes were untreated and served as the monocular contralateral control (MCC) group; (3) control group (CG), in which the animals grew four weeks, but received no manipulation. Animals in each group were evenly divided for DNA methylation assay and quantitative PCR (qPCR). After eye enucleation, the sclerae were harvested for DNA methylation assay and qPCR. The DNA methylation pattern in the promoter and exon regions of IGF‐1 and MMP‐2, along with the mRNA expression level of them, were determined by base‐specific cleavage and mass spectrometry and qPCR, respectively. Results: After four weeks of form‐deprivation, DNA methylation at 4/8 cytosine‐guanine sites in the IGF‐1 promoter was significantly lower in the MDT eyes than in the MCC or CG eyes. In addition, the level of IGF‐1 mRNA was moderately higher in MDT eyes compared to the MCC eyes and CG eyes. DNA methylation at 4/14 cytosine‐guanine sites in the MMP‐2 gene was very low, and no significant change was observed between the MDT eyes and the MCC or CG ones. However, the level of MMP ‐2 mRNA in MDT eyes was significant higher compared with MCC eyes and CG eyes, with an increase of 217% and 222%, respectively. Conclusions: In our guinea pig model of form‐deprivation myopia, the methylation of four cytosine‐guanine sites in the IGF‐1 gene promoter was significantly lower in the sclera after four weeks of MDT, and the transcription level of scleral IGF‐1 was moderately higher. Hence, the IGF‐1 gene methylation might play a role in the pathogenesis of form‐deprivation myopia in guinea pigs. The level of MMP‐2 mRNA in the sclera of MDT eyes was significantly higher, but not regulated by the methylation pathway, as the methylation status of MMP‐2 was unchanged.